Histoire Generale de La Societe des Missions- Etrangeres - Launay, Adrien (Tequi, Libraire-Editeur, 1894)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage